Effect of Dialysate Sodium Profiling on Blood Pressure in Haemodialysis Patients in Haemodialysis Center in 2019-2020 - سليمان ابراهيم; الجمل محمد (Latakia University Journal -Medical Sciences Series, 2021)
Introduction: Intra-Dialytic hypotension (IDH) is one of the most common complications during hemodialysis sessions in chronic hemodialysis patients. Sodium profiling is one of many available therapeutic choices to prevent IDH. We aimed in this study to know effects of sodium profiling on blood pressure and Inter-dialytic weight gain (IDWG) in chronic hemodialysis patients. Methods: We studied 93 patients (55 male, 38 female), aged 51.17 ± 15.05 (SD) years that undergo hemodialysis sessions regularly in Tishreen University Hospital during the period from 05/2019 to 11/2019. We have three modes of sodium profiling (mode 1:135 mEqł – mode 2:145 – 135 mEqł Linear – mode 3:148 – 138 mEqł Linear) each patient had 8 sessions in every mode (744 sessions for all patients in each mode, 2322 sessions in entire study period) with monitoring of: systolic and diastolic blood pressure pre- and post-dialysis, IDWG in every session, incidence of IDH if it happened and periodic blood tests. Results: There were statistical differences in Δ SBP (pre- and post-dialysis systolic blood pressure) (mode 1 = 16.00 ± 3.6 mmHg, mode 2 = 22.29 ± 3.5 mmHg, mode 3 = 11.48 ± 4.8 mmHg) (P.value < 0.001), also there were statistical differences in IDWG (in mode 1 = 2.69 ± 1.03 kg, in mode 2 = 2.67 ± 1.01 kg, in mode 3 = 3.03 ± 1.03) (P.value < 0.01), and there were statistical differences in incidence of IDH (65 sessions in mode 1 (8.73%), 112 sessions in mode 2 (15.05%), 39 sessions in mode 3 (5.24%) (P.value < 0.01), there was also weak correlation R = 0.34 between (DM) Diabetes Mellitus and incidence of IDH in Mode 1 (P.value < 0.001), and moderate correlation R = 0.52 in Mode 2 (P.value < 0.001), and moderate correlation R = 0.63 in Mode 3 (P.value < 0.001), and we found weak correlation R = 0.24 between hypertension and the incidence of IDH in Mode 3 (P.value < 0.001), we also found a relationship between dialysis vintage and IDWG and IDWG% which increase the incidence of IDH in Mode 1 (OR = 1.39, P.value = 0.013) and in Mode 2 (OR = 1.48, P.value = 0.007) and in Mode 3 (OR = 1.48, P.value = 0.049). Conclusions: We can use sodium profiling maneuvers to reduce the incidence of IDH and control of IDWG; but with caution in: DM, high dialysis vintage patients, hypertension.